(untitled) (Philological Studies, 2024)
The analysis of ecocriticism in literature emphasizes the presence of ecology in literature and the relationship between humans and nature. This paper considers the concepts of anthropocentrism, ecological awareness, and the ecocritical approach to literature as an ecosystem and, through socio-semiotic analysis, explores how signs and representations construct meaning within the picturebook Something Green by Aleksandra Bezmarević-Stević illustrated by Strahinja Simić. The choice of social semiotics and multimodal theory as a theoretical framework for analyzing the picture book was made to achieve a better understanding of the social and cultural aspect of the literary work. The goal is to contribute to understanding how literature can actively promote ecological awareness, especially in the context of children’s literature in Serbia, through the analysis of the picture book, besides recognizing and deciphering various socio-cultural symbols. The methods used in this paper are the analysis of four selected spreads within the picture book that are important for understanding the ecological issues the book addresses, and then synthesizing the interpreted symbols offered within socio-semiotic resources and finding their position in the reader’s experience. In the conclusion, we will provide a brief overview of the theoretical framework of the paper, revise the analytical part, and express an opinion on understanding the contribution of the picture book to the ecocritical literary category.